Kompetensi Komunikasi Guest Service Agent Dalam Mendorong Kepuasan Tamu Mh Hotel Ipoh Malaysia - Fery Harianto; Ohorella, Noviawan Rasyid; Dalimunthe, Maulana Andinata (Komunika, 2023)
The purpose of this research is to see how the communication competence of Guest Service Agents increases guest satisfaction at Mh Hotel Ipoh, Malaysia. Remembering that satisfaction is the basis for realizing organizational goals. Satisfaction encourages the creation of a conducive communication climate so that it provides its own incentives for achieving the organizational goals of Mh Hotel. The research method used in this research is a qualitative approach with a case study method as the author's perspective in analyzing the optimization of the use of Guest Comment Cards in encouraging communication satisfaction for guests of Mh Hotel Ipoh, Malaysia. The results of the research show that Guest Service Agents demonstrate communication competence in terms of service by welcoming and greeting every guest who comes to the hotel, then registering guests, finding rooms that are ready to be occupied based on guests' suggestions or requests, giving or issuing room keys, and also provide information for guests regarding services or facilities available at the hotel as well as information outside the hotel. Even though they have the ability to provide services to guests, these guest service agents often encounter obstacles in their work process. These obstacles include the emotional feelings that guests have, so they tend to be impatient in receiving and waiting for explanations from guest service agents.